Negotiating Malay Islamic Identity in the Era of Globalization: A Literature Review of Islamic Educational Institutions - Hafizul Husni; Fajri Ismail; Indah Wigati; Yuniar (Sustainable, 2026)
Globalization has significantly influenced cultural interactions and educational systems, creating both challenges and opportunities for the preservation of local cultural identities. In Southeast Asia, Malay Islamic identity represents a unique synthesis between Islamic religious values and Malay cultural traditions that has developed through historical processes of cultural interaction. The rapid expansion of globalization, including technological advancement, cultural exchange, and educational modernization, has raised important questions about the sustainability of this identity in contemporary society. This study aims to analyze how Islamic educational institutions respond to the integration of Malay Islamic identity in the era of globalization. This research employs a qualitative literature review method by examining academic publications published between 2020 and 2025. Data were collected through Google Scholar using keywords related to Islamic education, globalization, and Malay Islamic identity. The selected literature was analyzed using thematic analysis to identify major patterns, conceptual frameworks, and scholarly debates related to the role of Islamic educational institutions in preserving cultural identity. The findings indicate that Islamic educational institutions play a significant role in maintaining Malay Islamic identity through several strategies, including the integration of local wisdom in educational curricula, the adaptation of traditional learning systems to modern educational approaches, and the reinforcement of religious and cultural values within institutional practices. Furthermore, the study shows that globalization does not necessarily lead to the erosion of local identity but may encourage cultural adaptation and identity negotiation that allow Malay Islamic traditions to remain relevant in the global era.